Redirection of the sacred: the intricacies of Islamic meaning - Mohd Yusof, Danial (Association of Muslim Social Scientists, 2001)
In the simulacra generating age of postmodemity, the hyper-reality of contemporary society and an “anarchic” sociality warrants an investigation into rampant consumerism, the decline of rationalist fundamentalism as the ideology of modernity and the plethora of resurgent-cum-resistant movements. With this scenario, the article attempts to ascertain the value of postmodemism to Islamic scholarship in resolving the dialectic of metanmtives and relativism, Muslim scholars must be vigilant of postmodemism as a western construct and redefine its experience through Islamic phenomenology by exploring the complexities of heterogeneity and principles of humanity as opposed to a radical postmodemism that negates humanity as a meta-narrative and the celebration of egocentricity. Islam’s “occidentalism” is not a mental projection of moral superiority against the “Other” but a progressive discourse aiming to discover a universally tolerant projection and manifestation of Islam’s ummatic body and a representation of its tradition in a new age of possibilities.